1988
DOI: 10.1007/bf00405666
|View full text |Cite
|
Sign up to set email alerts
|

Work at sea: a study of sleep, and of circadian rhythms in physiological and psychological functions, in watchkeepers on merchant vessels

Abstract: Sleep length and sleep quality scores were collected on board ships over periods of up to two weeks from 38 watchkeepers working a '4-on/8-off routine' and 29 dayworkers. All watchkeepers exhibited fragmented sleeping patterns, which indicated a lack of adaptation of the sleep/wakefulness cycle to the hours of work. There were only slight differences in total sleep length between watchkeepers and dayworkers, however, both groups did not obtain an adequate amount of sleep. Within the watchkeeping crews the 3rd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 8 publications
2
16
1
Order By: Relevance
“…In particular, the studies of Rutenfranz et al (1988) reported average sleep durations of 7.4 -7.5 h, nearly an hour greater than the 6.6 h obtained in the current study. Similarly, their average work durations were between 9.4 and 10.4 h, in distinction to the average of 11.5 h in the current study.…”
Section: Maritime Schedules and Sleep Adequacycontrasting
confidence: 85%
See 2 more Smart Citations
“…In particular, the studies of Rutenfranz et al (1988) reported average sleep durations of 7.4 -7.5 h, nearly an hour greater than the 6.6 h obtained in the current study. Similarly, their average work durations were between 9.4 and 10.4 h, in distinction to the average of 11.5 h in the current study.…”
Section: Maritime Schedules and Sleep Adequacycontrasting
confidence: 85%
“…Rutenfranz et al (1988) also observed that personnel on the 04.00-08.00 watch were limited to a single sleep episode 20'% of the time. A similar percentage (22%) was obtained in this study; these sleep episodes resulted in less than 4 h of sleep in the 24-h period.…”
Section: Maritime Schedules and Sleep Adequacymentioning
confidence: 95%
See 1 more Smart Citation
“…Only primary, peer-reviewed articles published in English were included, while studies examining pharmacological interventions were excluded. From this search, we identified 22 papers which examined LWSW (17)(18)(19)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), two pairs of which overlap (25,29,36,37), leaving a total of 20 independent studies. The identified studies are summarized in table 1.…”
Section: Search and Inclusion Criteriamentioning
confidence: 99%
“…Eight of the studies identified in this review used a within-subject's design (18,22,23,25,29,(36)(37)(38), ten a between-subject's design (17,24,26,27,30,31,34,35,39,40), and four employed a mixed within-and between-subjects design (19,28,32,33). Seventeen studies were field-based (17-19, 22, 24-32, 34-37) and five used laboratory simulations (23,33,(38)(39)(40).…”
Section: Schedules and Participantsmentioning
confidence: 99%